2005
DOI: 10.1063/1.1935044
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-confined Stark effect in a single InGaN quantum dot under a lateral electric field

Abstract: The effect of an externally applied lateral electric field upon an exciton confined in a single InGaN quantum dot is studied using microphotoluminescence spectroscopy. The quantum-confined Stark effect causes a shift in the exciton energy of more than 5 meV, accompanied by a reduction in the exciton oscillator strength. The shift has both linear and quadratic terms as a function of the applied field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 16 publications
(23 reference statements)
3
21
2
Order By: Relevance
“…We have yet to achieve higher nanostructure densities using this method, making it perhaps less appropriate to the construction of LEDs than to the study of single nitride quantum dots, in which context samples grown in this way have proved extremely useful [4,5]. Looking at Fig.…”
mentioning
confidence: 96%
“…We have yet to achieve higher nanostructure densities using this method, making it perhaps less appropriate to the construction of LEDs than to the study of single nitride quantum dots, in which context samples grown in this way have proved extremely useful [4,5]. Looking at Fig.…”
mentioning
confidence: 96%
“…However, the analysis of coupled InGaAs QDs shows that, due to strain relaxation in the structure, the In composition of the upper QD is higher than in the lower one. 11 Since InGaN QD structures with 20%-25% In have been reported in the literature, 12 we assume an In content of 20% in the lower dot and 25% in the upper dot. Based on the experimental data in Ref.…”
mentioning
confidence: 99%
“…However, only a few recent studies have reported such measurements on GaN/AlN [57,58] and InGaN/GaN QDs [59,60]. It was found that a vertical electric field can result in an almost linear blue shift of the optical transition of up to 100 meV in GaN/AlN QDs [58] due to the partial compensation of the in-built field and the dominant effect from the induced permanent dipole.…”
Section: Quantum-confined Stark Effect (Qcse)mentioning
confidence: 99%